Biochemical responses of crayfish exposed to imidacloprid: assessment of oxidative stress, osmoregulatory response and neurotoxicity - Yologlu, Ertan; Uckun, Mirac; Uckun, Aysel Alkan; Oz, Ozden Barim (Taylor & Francis Ltd, 2025)
Among the nicotinoid insecticides, imidacloprid (IMI) may affect non-target invertebrates like aquatic crustaceans by entering the aquatic environment through rainfall. Nevertheless, there are not sufficient studies on the toxicity mechanism of IMI in crayfish. Here, we investigated the effects of IMI on oxidative stress, osmoregulatory, and neurotoxicity biomarkers. The 96-hour lethal concentration value (96 h-LC50) of IMI was determined to be 0.932 mg AI L-1. Four concentrations of IMI (0.932, 0.466, 0.233 and 0.117 mg AI L-1) were applied to crayfish for 96 h. Na+/K+-ATPase, Mg2+-ATPase, Ca2+-ATPase, and total ATPase activities had almost significantly concentration-related inhibition in both gill and muscle tissues (p < 0.05). Compare with control in hepatopancreas, the activities of GST, SOD and GPx were increased, while the activities of AChE, CES and GR were decreased (p < 0.05). As non-enzymatic parameters, a statistically significant (p < 0.05) increase in MDA levels and a decrease in GSH levels were observed in the hepatopancreas compared to the control group, which was not related to the concentration. In conclusion, it can be said that the study's biomarkers are highly helpful and that commercially consumed crayfish are a significant non-target organism in the assessment of IMI toxicity.
Keywords: Crayfish; esterases; imidacloprid; osmoregulatory system; toxicity